Tangerine and mango fruits quality detection by near infrared spectroscopy - Theanjumpol P. (Chiang Mai University, 2015)
Near infrared spectroscopy (NIRS) appears a prominent technique for non-destructive fruit quality assessment. This research work was focused to evaluate the use of NIRS in detection of the quality characteristic of Thai fruit such as chemical properties and physiological disorder. Two kinds of Thai fruit, tangerine and mango were used in this research. Tangerine and mango fruits were harvested at the commercial maturity and transported to Postharvest Technology Research Institute, Chiang Mai University. The fruits were measured the spectra by using NIRSystem6500 in wavelength range 700-1100 nm. Total soluble solid (TSS) and titratable acidity (TA) were determined by digital refractometer and titrated with 0.1 N sodium hydroxide. Before calibration, the spectral data were transformed with the various of mathematical techniques and the prediction models were developed based on partial least square regression (PLSR). Physiological disorder detection, mango fruits were kept in the chamber at 5±1°C to induce the chilling injury symptom. NIRSystem6500 was used to measure the spectra of fruits in wavelength region from 700 nm to 1100 nm and then, determined the electrolyte leakage of the flesh at initial time on days 15 and 30. Spectral data were analyzed by using principle component analysis (PCA). NIRS could be used to detect the quality of both fruits, tangerine and mango, in term of TSS and TA. The PLSR models contained the correlation of determination about 0.7-0.9. Moreover, it was found that chilling injury of mango fruit responded differently to near infrared. It could be separated into two groups with PC2 and PC3. The first group was the spectrum of normal mango: no chilling injury symptom. The second group was the spectrum of mango which had been kept at 5±1°C for 15 and 30 days and showed severe chilling injury symptom; similar to the electrolyte leakage of the flesh which increased from 8.6% at the initial time to 15.4% and 13.0% when the mangoes were kept at 5±1°C for 15 and 30 days, respectively.